(untitled) (Community Based Medical Journal, 2014)
A clinical trial was carried out with thirty patients affected with vitiligo. Repigmentation was observed in 26.7% cases on the first follow up visit. At the end of 4th week with tacrolimus ointment in the next visit, it was perceptible in 15 cases 50.1% and after 12 weeks of therapy 83.3% yielded repigmentation. Among those who had repigmentation, 20% had > 75% repigmentation, 23.3% had 50-75% repigmentation. The percentage of repigmentation on head and neck (83.3%) was greater than that on extremities (55.6%). Complete (>75%) repigmentation was 33.3% cases on head and neck and 26.7% along with extremities. A total of 83.3% cases had some repigmentation and among them, 10 cases had focal presentation and 15 cases had generalised or segmental presentation. There was statistically significant (p<0.005) difference observed between presentation and pigmentation. By using topical steroid minimum side effects like pruritus in 6.7% cases and burning in 10% cases were evidenced. This study reflects that tacrolimus ointment 0.1% is an effective topical therapeutic option for vitiligo especially on the head and neck region with minimum side effects. CBMJ 2014 January: Vol. 03 No. 01 P: 4-7